2020
DOI: 10.1371/journal.pone.0240064
|View full text |Cite
|
Sign up to set email alerts
|

Superficial capillary perfusion on optical coherence tomography angiography differentiates moderate and severe nonproliferative diabetic retinopathy

Abstract: Purpose To identify objective optical coherence tomography angiography (OCTA) parameters that characterize the spectrum of non-proliferative diabetic retinopathy (NPDR), especially those that distinguish moderate from severe NPDR. Methods Sixty eyes of 60 patients with treatment-naïve NPDR (mild: 21, moderate: 21, severe: 18), 23 eyes with diabetes and no retinopathy, and 24 healthy control eyes were enrolled. OCTA slabs were segmented into superficial (SCP), middle (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…As corroborated extensively in the literature, FAZ size increases with the progression of DR (Figure 4) [71,74,78,[100][101][102][103]. Several of these studies evaluated the FAZ of the SCP and DCP separately.…”
Section: Faz Area and Faz-related Measurementssupporting
confidence: 64%
See 2 more Smart Citations
“…As corroborated extensively in the literature, FAZ size increases with the progression of DR (Figure 4) [71,74,78,[100][101][102][103]. Several of these studies evaluated the FAZ of the SCP and DCP separately.…”
Section: Faz Area and Faz-related Measurementssupporting
confidence: 64%
“…Analysis of the MCP as a distinct vascular layer opened a window of opportunity to understand how DR may have spatially unique impacts. In general, studies have found that trends within the MCP mirrored those occurring at the SCP and DCP; as DR severity increased, VD and VLD both decreased [76][77][78]. Interestingly though, DR severity had different effects on the vascular layers.…”
Section: Perfusion and Vessel Densitymentioning
confidence: 96%
See 1 more Smart Citation
“…However, Ong et al [ 40 ] described the utility of VD evaluation, the FAZ and the vessel length density at the SCP to distinguish healthy subjects and the different stages of nonproliferative DR (NPDR). They suggested that SCP changes are more reliable due to the lower noise and artefacts in OCTA acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of projection-resolved (PR) OCTA algorithms [ 36 , 37 ] and 3D visualization [ 38 ] systems has increased the quality of depth-resolved OCTA scans. Indeed, while in 2D reconstructions, retinal layers are segmented and reconstructed by two topographic axes (i.e., x and y ), volume-rendered OCTA reconstructions integrate structural and angiographic data to create 3D images.…”
Section: Wf-octa and Nonperfusion Areas In Drmentioning
confidence: 99%